High Prevalence and Widespread Distribution of Zoonotic Enterocytozoon bieneusi Genotypes in Swine in Northeast China: Implications for Public Health. (23rd September 2015) - Wan, Qiang; Lin, Yongchao; Mao, Yixian; Yang, Yuqi; Li, Qiao; Zhang, Siwen; Jiang, Yanxue; Tao, Wei; Li, Wei
Abstract: This study analyzed 563 fecal specimens of asymptomatic pigs from five cities of northeast China for the prevalence and genetic characteristics of Enterocytozoon bieneusi . The parasite was detected in 267 of 563 (47.4%) pigs by nested PCR of the ribosomal internal transcribed spacer (ITS). The differences in prevalence between preweaned (58.0%, 94/162) and growing pigs (39.6%, 114/288) and between weaned (52.2%, 59/113) and growing pigs are significant ( p  <   0.05). Genotypic typing and phylogenetic analysis facilitated identification of six human‐pathogenic genotypes EbpC, O, CS‐4, EbpA, Henan‐IV, and PigEBITS5 and six potentially zoonotic genotypes EbpB, CC‐1, CS‐1, CS‐3, CHN7, and CS‐10. Genotypes CS‐4 (32/35) and EbpC (3/35) from Harbin and Henan‐IV (5/64) from Qiqihar determined in pigs herein represented the main causative agents of human microsporidiosis in Harbin. The most dominant genotype EbpC found in pigs from Daqing (35/65) and Qiqihar (a close neighbor to Daqing) (47/64) contributed significantly to human infections in Daqing. Genotype EbpC was also a leading E. bieneusi pathogen in humans, drinking water, and wastewater in central China. This study provided robust evidence that pigs could be an outstanding source of human microsporidiosis and water contamination in China.